Distribution of Thylakoid Proteins between Stromal and Granal Lamellae in Spirodela : Dual Location of Photosystem II Components - Callahan, Franklin E. (1989)
We have quantified the lateral distribution of 12 thylakoid proteins of Spirodela oligorrhiza by immunoblot analysis of detergent-derived granal and stromal lamellae. The immunological, ultrastructural, cytochemical, and biophysical measurements each indicated the expected overall separation of photosystem II (PSII) and photosystem I (PSI) components; however, certain proteins were not completely localized to one lamellar fraction. The apoproteins of the light harvesting chlorophyll a/b complex, subunit 1 of PSI and the components of the PSII reaction center (the 32 kilodalton, D2, and cytochrome b(559) proteins) were dually located between granal and stromal lamellae. Proteins associated exclusively with one of the membrane types were: in granal lamellae, the 43 and 51 kilodalton PSII proteins, and in stromal lamellae, the α and β subunits of the proton ATPase.